A Note on the Effect of Microwave Heating on Iodine-Catalyzed Acetylation of Wood. (3rd May 2016) - Eranna, Prasad B.; Pandey, Krishna K.; Nagarajappa, Giridhar B.
Abstract : The effect of microwave heating on the iodine-catalyzed acetylation of rubberwood with acetic anhydride has been investigated. Microwave radiation was used as the heating source for modifying specimens saturated with acetic anhydride in bulk solution (excess of reagent) and impregnated specimens (limited supply of anhydride). Extent of modification of wood was expressed in terms of weight percent gain (WPG) and modification was characterized using FTIR spectroscopy. In bulk solution, microwave radiations were primarily absorbed by anhydride solutions for heating purposes and a moderate WPG was obtained. However, when microwave heating was used to modify impregnated wood specimens under no excess of anhydride, a significant enhancement in degree of modification was achieved within a few minutes. The modified wood exhibited good anti-swelling efficiency.